(untitled) (Academicia Globe: Inderscience Research, 2021)
The article presents a research analysis directed to the development of new scientific and technical bases of resurstejamkor technologies and technical means of their implementation in the improvement of melioration of irrigated crop areas and the effect of leveling on fertility and the organization of the leveling process.